The Efforts for Coastal Community Welfare Improvement and Economic Development Acceleration in Bali Province - Riana, I. Gede; Wiagustini, Ni Luh Putu; Meydianawathi, Luh Gede (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
This study aims to produce a Master Plan draft for fishery-based MSME Development in Bali. This study consists of five study processes, among potential analysis of Micro Small and medium-sized enterprises (MSMEs), and business climate analysis, an analysis of the MSME builder institution roles, and the master plan preparation of fishery-based MSMEs in Bali. The potential of fishery-based MSMEs in Bali is poured on geographic information systems (GIS); Based on the Multiple regression analysis, it can be seen that GDP growth and labour has positive effect on the productivity levels of MSMEs; Based on Importance-Performance Analysis, there are approximately five attributes (50%) supporting the successful development of MSMEs located in quadrant III, this means that fishermen in Bali have the perception that five of these attributes are forms of government services (related institution) to the fishery-based MSMEs which should serve as the main priority; Based on AHP Analysis, it is found that the need for the fishery development in fishery-based MSMEs in Bali covers several operational, capital and market access aspects. By the potential analysis of MSMEs and development target program, it has been compiled development master plan matrix of fishery-based MSMEs and development master plan matrix for related sectors with the fishery-based MSMEs in the Bali Province 2015-2019.